Bootstrap Selling The Sandler Way Or - Morrison, Bill (Ascent Audio, 2020)
At some point, good salespeople learn the difference between simply "doing the job" . . . and accepting the personal responsibility to produce certain results. This book focuses on "Bootstrap Selling," which is all about becoming fully accountable for sales behaviors. You might have a large team around you, and you could have a great and supportive boss. Yet the difference between a self-starting, high-performance bootstrapping sales professional and an order-taker is that the bootstrapper knows personal commitment and acceptance of responsibility makes good things happen-and acts accordingly. Herein you will find nineteen career-changing lessons in Bootstrap Selling the Sandler Way.